Connection of European particle therapy centers and generation of a common particle database system within the European ULICE-framework - Eitz, Kerstin Anne; Bougatf, Nina; Habermehl, Daniel; Oetzel, Dieter; Debus, Jürgen; Combs, Stephanie (Radiation oncology, 2012)
To establish a common database on particle therapy for the evaluation of clinical studies integrating a large variety of voluminous datasets, different documentation styles, and various information systems, especially in the field of radiation oncology.